Relevansi Teori Multiple Intellegences dengan Undang-Undang Sistem Pendidikan Nasional Tahun 2003 - Mufrih Almunadi; Azhar Azhar (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2022)
Howard Gardner's idea about the existence of multiple intelligences or multiple intelligences which he outlined in his book